Non-canonical Helitrons in Fusarium oxysporum. Issue 1 (December 2016) - Chellapan, Biju; van Dam, Peter; Rep, Martijn; Cornelissen, Ben; Fokkens, Like
Abstract Background Helitrons are eukaryotic rolling circle transposable elements that can have a large impact on host genomes due to their copy-number and their ability to capture and copy genes and regulatory elements. They occur widely in plants and animals, and have thus far been relatively little investigated in fungi. Results Here, we comprehensively survey Helitrons in several completely sequenced genomes representing theF. oxysporum species complex (FOSC). We thoroughly characterize 5 different Helitron subgroups and determine their impact on genome evolution and assembly in this species complex. FOSC Helitrons resemble members of the Helitron2 variant that includes Helentrons and DINEs. The fact that some Helitrons appeared to be still active in FOSC provided the opportunity to determine whether Helitrons occur as a circular intermediate in FOSC. We present experimental evidence suggesting that at least one Helitron subgroup occurs with joined ends, suggesting a circular intermediate. We extend our analyses to other Pezizomycotina and find that most fungal Helitrons we identified group phylogenetically with Helitron2 and probably have similar characteristics. Conclusions FOSC genomes harbour non-canonical Helitrons that are characterized by asymmetric terminal inverted repeats, show hallmarks of recent activity and likely transpose via a circular intermediate. Bioinformatic analyses indicate that they are representative of a large reservoir of fungal Helitrons that thus far has not been characterized.